UMP placed in 2019 QS World University Rankings by subject - UMP, PNC (2019)
Universiti Malaysia Pahang (UMP) can now stand tall among the world’s elite universities after it is listed in the QS World University Rankings by Subjects 2019 for three categories: Engineering (Chemical), Engineering-Mechanical Aeronautical and Manufacturing, and Engineering and Technology.